A quality assessment of orthodontic patient information leaflets - Jadbinder Seehra; Laura Cockerham; Nikolaos Pandis (SpringerOpen, 2016)
Abstract Background Patient information leaflets (PILs) are often used to reinforce and provide further information relating to treatment choices, risks, and alternatives. An assessment of the quality of commonly used orthodontic patient information leaflets is lacking. Methods A cross-sectional assessment of patient information leaflets from two international orthodontic societies was undertaken. The quality of each leaflet was assessed using the DISCERN instrument. The readability of each leaflet was assessed using the Flesch Reading Ease instrument, Flesch-Kincaid Grade Level and Simple Measure of Gobbledygook (SMOG) index. Descriptive statistics followed by univariate analysis was conducted. Results Thirty-six patient information leaflets were identified. Reporting of DISCERN instrument items relating to aims, description of sources, details of additional sources, consequences of no treatment, possible treatment options, and support for a shared decision process was of low quality. The overall quality score for the total sample was 44. The median Flesch Reading Ease, Flesch-Kincaid Grade Level, and SMOG index scores were 70 (interquartile range (IQR) 53.3-73.9), 7.2 (IQR 6-9.7), and 7.3 (IQR 6.7-9.1), respectively. There was a significant difference between the quality (−8.00, 95 % CI: −14.62, −1.38, p < 0.001), Flesch Reading Ease (−22.30, 95 % CI: −26.77, 17.83, p < 0.001) and the Flesch-Kincaid Grade Level (3.80, 95 % CI: 2.74, 4.86, p < 0.001) scores between the two societies' PILs. Conclusions In relation to the DISCERN instrument, the quality of orthodontic PILs is deemed of moderate quality. There is a significant difference between the quality scores and the readability of PILs from different societies.